Pengaruh Motivasi Komunikasi Interpersonal Dan Pengalaman Praktik Kerja Lapangan Terhadap Kesiapan Mahasiswa Memasuki Dunia Kerja - Ida Farida; Muhammad Ridwan Basalamah; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract In today's challenging and competitive age of globalization, a great need for qualified human resources, abilities, knowledge and skills tailored to its needs is met, as the world's demand for prospective workers is increasingly high.The purpose of this research is to describe the motivation, interpersonal communication, and field practice experiences, to know and analyze the effects of motivations, interpersonal communication, and field practice experiences on student preparedness to enter the workforce, to know and analyze the motivating effects on student preparedness to enter the workforce, To know and analyze the effects of interpersonal communication on students' preparedness to enter the workforce, to know and analyze the effects of field practice experiences on student preparedness to enter the workforce. Research shows that motivation, interpersonal communication and field practice experiences are simultaneously positive and significant to the preparedness variables in the work world, motivation has a positive and significant impact on preparedness to enter the work world, interpersonal communication has a positive and significant impact on preparedness to enter the work world, Field practice experiences have hada positive and significant impact on preparedness to enter the work world. Keyword : Motivation, Interpersonal communication, field practice, and preparedness.